The Gontor Way: Bringing Islamic Education to Sulawesi - Wekke, Ismail Suardi; Riswandi, Akmal (Shautut Tarbiyah-IAIN Kendari, 2024)
Beyond its renowned Ponorogo campus, the esteemed Islamic boarding school, Pondok Modern Darussalam Gontor (Gontor), has established a firm presence in Sulawesi. This abstract delves into Gontor's journey and impact across the diverse island, exploring its two established branches. Pondok Modern Darussalam Gontor 7 "Riyadhatul Mujahidin" in Kendari, Southeast Sulawesi, offering a comprehensive Islamic education program since 2002. Pondok Modern Darussalam Gontor Putri 4 & 6 in Konawe Selatan and Poso Pesisir, respectively, nurturing young women with Islamic values and academic excellence. This abstract sheds light on Gontor's contributions to Sulawesi, including: Expanding access to quality Islamic education for both boys and girls. Promoting interfaith dialogue and understanding within diverse communities. Cultivating responsible and well-rounded future leaders imbued with Islamic principles. Sparking social and economic development through its presence and activities. This abstract serves as a brief yet informative introduction, piquing the reader's interest to learn more about Gontor's thriving influence in Sulawesi.keywords: Gontor, Islamic Education, Boarding School.